Diaphragm-Sparing Nerve Blocks for Shoulder Surgery. Issue 4 (August 2017) - Tran, D. Q.; Elgueta, M. F.; Aliste, J.; Finlayson, R. J.
Abstract : (Abstracted from Reg Anesth Pain Med, 42(1):32–38, 2017) The main aim of this article is to arrive at feasible diaphragm-sparing alternatives to interscalene brachial plexus blocks (ISBs) that can provide satisfactory surgical local anesthesia and postoperative pain relief with a low incidence of hemidiaphragmatic paralysis. The most common adverse effect of ISB for standard post–shoulder surgery analgesia is the occurrence of ipsilateral phrenic nerve block which causes a hemidiaphragmatic paralysis in 100% of patients and a 27% decrease in the patients forced vital capacity and forced expiratory volume at 1 second.